Драгоценности Рюриковичей по памятникам письменности (элементы одежды) - Bożena Hrynkiewicz-Adamskich (Studia Rossica Posnaniensia)
The aim of the article is to present the names of the valuables in testaments of the Russian great and appanage princes of the 14th-16th century. Special attention has been paid to clothing terminology (names of textiles, colours and dyes, individual garments, clothing details). Lexicographical and etymological data, as well as a semantic classification of dress and clothing detail names are provided. According to Jean Baudrillard, far from the primary status of an object being a pragmatic one, it is the sign exchange value which is fundamental. Thereupon, the attempt to present the social meaning and the unconscious discourse of the valuables mentioned in the testaments of the Rurik dynasty members is also made in this article.